Ouvir, interagir e criar: a composição musical como oportunidade de humanização das relações sociais em uma orquestra comunitária - Tagliaro, Lenon Raul (Universidade Federal de São Carlos, 2018)
This research had as its theme the creation of composition and musical arrangement for a community orchestra, whose participants had a significant diversity of mastery and musical knowledge. The aim of this work was to investigate whether the creation of arrangements and compositions could offer a space / condition of musical participation more dynamic and adequate to the musical abilities and potentials of the participants, considering both the individual desires and capacities as well as the small groups that integrate the orchestra. Authors such as Araújo, Brandão and Freire were used to refer to educational processes; Almada, Cooper, Sotelo, and others were referential for the musical aspects; Joly, Higgins, Kater, Koellreutter and others were the basic authors for the concepts of musical education. The main objective was to describe and understand how a dialogical action in the elaboration of arrangements and musical compositions for this community orchestra can contribute in the process of better participation and integration of the musicians in the rehearsals and concerts. The specific objectives were also to improve social and musical relations in the community group; the preparation of a composition and arrangement more appropriate to the technical level of the orchestra participants; and the description of the strategies of musical writing that enabled the preparation of scores in levels of execution appropriate to the orchestra in question. The research developed as a qualitative study, and the option of using action research was made. As a data collection instrument, participant observation and conversation were chosen, in order to observe the orchestra's rehearsals and listen to the members' perceptions. The results pointed to the educational processes resulting from the collective musical practice, the initial formation of the musicians, among other aspects related to socialization and personal improvement.
Keywords: Processos educativos; Orquestra comunitária; Composição e arranjo; Educational processes; Community orchestra; Composition and arrangement; CIENCIAS HUMANAS::EDUCACAO